Rodolphe Lemieux et le Parti libéral, 1866-1937: le chevalier du roi - Castonguay, René (Presses de l'Université Laval, 2000)
Keywords: Partis politiques

From Bourassa to Bourassa: Wilderness to Restoration - MacDonald, L. Ian (McGill-Queen's University Press, 2002)
"From Bourassa to Bourassa is a narrative history of the Quebec Liberal Party during its wilderness years after the 1976 election of the Parti Quebecois and its subsequent restoration in 1985." "First published to critical acclaim in 1984, From Bourassa to Bourassa, 2nd edition, updates the story with Bourassa's landslide election victory in 1985 and his subsequent role in the Meech Lake Accord and the Canada-U.S. Free Trade Agreement, the two issues that largely defined the decade of the 1980s for Quebec and for Canada."–BOOK JACKET.
Keywords: Bourassa; Robert; Partis politiques

René Lévesque and the Parti Québécois in Power - Fraser, Graham (McGill-Queens University Press, 2001)
Keywords: Lévesque; René; Partis politiques

"Le Germe de la liberté": les républicains du Bas-Canada et les révolutions européennes de 1848 - Dzanic, Dzavid (Mens, 2008)
issued: 2008-23-00
Keywords: Idéologies; Partis politiques; Rouges

Le Front d’action politique (FRAP) à Montréal: de la naissance aux élections (1969-1970) - Comby, Marc (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2001)
Number: 2
Keywords: Groupes populaires; Partis politiques; Élections

La carrière polyvalente de Gustave Francq, figure marquante du syndicalisme international au Québec (1871-1952) - Leroux, Éric (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2000)
issued: 2000-23-00
Keywords: Conseil des métiers et du travail de Montréal; Parti ouvrier; Partis politiques

Un singulier cousinage Louis-Joseph Papineau et Jacques Viger - Beaudoin, Léo (Montréal en tête, 2009)
issued: 2008-21-00
Keywords: Députés; Maires; Papineau; Louis-Joseph; Partis politiques; Viger; Jacques

Mouvements sociaux, syndicats et action politique à Montréal: l'histoire du FRAP (1970-1974) - Comby, Marc (Université de Montréal, 2005)
Keywords: Crise d'octobre; Drapeau; Jean; Groupes populaires; Partis politiques; Élections

L'expérience du FRAP à Montréal (1970-1974). La tentative de créer au Québec un parti d'extrême gauche - Comby, Marc (Contester dans un pays prospère: l'extrême gauche en Belgique et au Canada, 2007)
Keywords: Crise d'octobre; Drapeau; Jean; Groupes populaires; Partis politiques; Élections